TRPM7 interference vector repaires injury caused by hypoxia/reoxygenation in cardiomyocyte cell line H9C2 - YANG Jue-sheng, FAN Hu-xiong, HU Shan, GAO Ri-feng, LU Fei, WANG Heng, TANG Yan-hua (Jichu yixue yu linchuang, 2020)
Objective To study the repair function and mechanism of TRPM7 interference vector in hypoxic myocardial cell line (H9C2). Methods The hypoxia/reoxygenation model of H9C2 cardiomyocytes was established and the TRPM7 interference expression vector was constructed to transfect H9C2 cells. The expression of HIF1-α and TRPM7 in H9C2 cells was detected by RT-qPCR and Western blot. [Ca2+]i and apoptosis was determined by flow cytometry. Results When H9C2 cells were transfected with TRPM7 interference vector, the expression of HIF1-α TTRPM7, the [Ca2+]i concentration and the apoptosis rate all decreased. Conclusions TRPM7 interference vector has significant repairing effect on hypoxia H9C2 cardiomyocytes, and the mechanism may be mediated PI3K/Akt pathway.